2009
DOI: 10.1002/mus.21502
|View full text |Cite
|
Sign up to set email alerts
|

Syrian hamster infected with Leishmania infantum: A new experimental model for inflammatory myopathies

Abstract: Idiopathic inflammatory myopathies (IIMs) are inflammatory disorders of unknown origin. On the basis of clinical, histopathological, and immunological features, they can be differentiated into three major and distinct subsets: dermatomyositis; polymyositis; and inclusion-body myositis. Although a few animal models for IIM are currently available, they lack several characteristic aspects of IIMs. The aim of our study was to examine skeletal muscle involvement in an experimental animal model of visceral leishman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Syrian hamsters also exhibit severe clinical signs and symptoms that are similar to those observed in naturally infected dogs and humans [23,24,36]. However, the absence of iNOS expression [10,28,31] and the suppression of lymphoproliferative responses [64,65] observed, lead us to argue that the hamster is a more suitable model for pathological studies of VL than for the evaluation of vaccine candidates.…”
Section: Remarks and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Syrian hamsters also exhibit severe clinical signs and symptoms that are similar to those observed in naturally infected dogs and humans [23,24,36]. However, the absence of iNOS expression [10,28,31] and the suppression of lymphoproliferative responses [64,65] observed, lead us to argue that the hamster is a more suitable model for pathological studies of VL than for the evaluation of vaccine candidates.…”
Section: Remarks and Discussionmentioning
confidence: 99%
“…In this context, BALB/c mice provide a better model of self-healing or subclinical infection than of disseminated visceral disease [10]. Paciello et al [36] reported that susceptible mouse strains do not reproduce progressive disease as observed in human active VL. Furthermore, the intensity of pathological changes in the visceral organs of BALB/c mice can vary depending on the initial inoculum size, as described above.…”
Section: Remarks and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those for which such an infiltration has been demonstrated are the model of crush-injury described above [7] and models designed to help understand the mechanisms of inflammatory myopathies that occur in man. In these latter cases, myositis is induced by various infectious agents [53, 54], immunization with muscle components, for example, myosin [55, 56], and intraperitoneal injections with lipopolysaccharide [57]. The TNF system has not been examined in any of these myositis models replicating the inflammatory myopathies seen in man.…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies used in this study included rabbit polyclonal Beclin-1 (BECN 1 H300: sc-11,427, Santa Cruz Biotechnology, Dallas, Texas, US), rabbit polyclonal LC3 (ab51520, Abcam, Cambridge, UK), mouse monoclonal APP (6E10) (SIG-39320, BioLegend, San Diego, California, US). The method was previously described [29]. Briefly, the primary antibody diluted in Phosphate Buffer Saline (PBS) was applied overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%